Mediating effect assessment of ifosfamide on limb salvage rate in osteosarcoma: A study from a single center in China - Li, Yan; Fu, Yiwei; Zhang, Zhaohui; Wang, Zhuo; Yin, Junqiang; Shen, Jingnan (Frontiers in Oncology, 2022)
Osteosarcoma is one of the most prevalent primary bone malignancies in children and adolescents. Surgery and chemotherapy are standard methods of osteosarcoma curation. Tumor mass volume after neoadjuvant chemotherapy, the nearest of blood vessels to the tumor, tumor volume shrinkage rate were important factors influencing osteosarcoma surgery options. It had been reported that ifosfamide may play an important role in reducing tumor mass volume in soft tissue sarcoma, but in osteosarcoma, we were not sure whether it had the effect and whether it may have influence on surgical options. We carried this retrospective study to in order to explore whether ifosfamide may affect the tumor mass volume of osteosarcoma and whether it elevates limb salvage rate of this kind of mesenchymal sarcoma.